2010
DOI: 10.1021/jp103317c
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Reaction of Methacrolein with Chlorine Atoms in 1−950 Torr of N2or N2/O2Diluent at 297 K

Abstract: The rate constant of the reaction of Cl atoms with methacrolein (k(1)) has been measured relative to that of Cl with propane (k(2)) or cyclohexane (k(6)) at ambient temperature and pressures varying from 1-950 Torr. The experiments were carried out by irradiation (350 nm) of Cl(2)/methacrolein/propane or cyclohexane mixtures in N(2) or N(2)/O(2) diluent at ambient temperature in a spherical (500 cm(3)) Pyrex reactor (GC/FID analyses) or a 140 L FTIR smog chamber. The measured relative rate constant ratios in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 23 publications
11
23
0
Order By: Relevance
“…As shown in Figure 10, the rate constant increases significantly with the pressure increasing from 1 to 10 Torr, and there is no discernible pressure dependence when P > 100 Torr. This finding is in good agreement with the experiment observations of Kaiser et al 28 …”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…As shown in Figure 10, the rate constant increases significantly with the pressure increasing from 1 to 10 Torr, and there is no discernible pressure dependence when P > 100 Torr. This finding is in good agreement with the experiment observations of Kaiser et al 28 …”
Section: Resultssupporting
confidence: 94%
“…This is in agreement with the experimental observations of Kaiser et al 28 So we will focus on the addition reaction of the CC double bond, the aldehyde-H and methyl-H abstraction reactions in the following kinetic calculation.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Birdsall et al51 also provide evidence for the formation of OH in the reaction of HO 2 with bicyclic peroxy radicals formed in the oxidation of aromatics, e.g.While some of this discrepancy may be related to artefactually high OH measurements in isoprenedominated environments,135 a great deal of recent effort has been expended on understanding the chemistry of isoprene-derived peroxy radicals, particularly in pristine regions of the atmosphere, where their fate is controlled in large part by reactions with HO 2 and by unimolecular reactions (see Section 3.8).While initial speculation regarding the missing HO x recycling chemistry centered on reactions of HO 2 with RO 2 radicals derived from reaction of OH with isoprene, 18 OH production appears to be minimal in these (and related) cases 123,136. Reactions of HO 2 with peroxy species derived from reaction of OH with methyl vinyl ketone and methacrolein, the two main isoprene oxidation products, appear likely to generate OH, however,124,137 and thus likely play a minor role in OH radical production / HO x recycling. Further studies of OH production from the reactions of HO 2 with the complex suite of organic radicals derived from other biogenic…”
mentioning
confidence: 99%
“…3, our study shows a systematic increase in the observed relative rate ratio for the reaction of Cl atom with cyclohexadiene, with increasing concentration of oxygen. Very recently, during the measurement of the rate constant of the Cl atom reaction with methacrolein with reference to propane, addition of 2-20% oxygen was found to increase the relative ratio by a statistically significant amount [20]. Such difference in the rate constant in the presence of air was suggested to be due to interference of the OH reaction, generated during the reactions of peroxy radicals with HO 2 , as observed in the Cl-initiated oxidation of acetaldehyde [21,22].…”
Section: Discussionmentioning
confidence: 99%